Vaginal flora in HPV infection: a cross‑sectional analysis - Peining Dou; Feng Fang; Rongqiu Qin; Jingsong Nie; Xiaoyan Chen; Xiaoyan Yin; Yiding Wang; Shengying Shi (Journal of Obstetrics and Gynaecology)
Objective The vaginal flora has been reported to be associated with human papillomavirus (HPV) infection. The purpose of this study was to investigate the characteristics of the cervical microbiota in patients with HPV infection and to analyse the changes in the vaginal flora and enzyme profiles in females with HPV infection.Methods We conducted a cross-sectional study involving 206 participants who underwent HPV genotyping, sexually transmitted diseases pathogen testing, cytology examination, and microbiome analysis. Additionally, we collected 115 HPV-negative samples and 48 HPV-positive samples for 16S rRNA amplicon sequencing. The vaginal microbial communities of both groups were analysed for diversity and differences to explore their association with HPV infection.Results The abundance of Lactobacillus was found to be reduced, while Gardnerella vaginalis was significantly more prevalent in the HPV + group. In terms of alpha diversity indices, the Shannon index (P = .0036) and Simpson index (P = .02) were higher in the HPV + group compared to the HPV − group, indicating greater community diversity in the HPV + group. Among the 10 sexually transmitted diseases pathogens analysed, Uup3 and Uup6 were significantly associated with HPV infection. Statistically significant differences were observed in Nugent scores and bacterial vaginosis between the two groups (P < .05). In functional analysis, 11 proteins and 13 enzymes were found to be significantly altered in the HPV + group.Conclusion Our study demonstrates that disruptions in the vaginal flora are associated with HPV infection. Reduced levels of Lactobacillus, increased prevalence of Gardnerella, and abnormal enzyme profiles are closely linked to HPV infection.